Forgiveness and Subjective Well-being in Students Who are Victims of Toxic Relationships - Michelle Kaelyn Joy; Arthur Huwae (Bisma The Journal of Counseling, 2025)
University students who experience toxic relationships frequently encounter challenges in achieving subjective well-being due to the psychological consequences of unhealthy relational dynamics. These difficulties may stem from an impaired capacity to forgive and to reconcile with the situation. This study aims to examine the association between forgiveness and subjective well-being among students who have been victims of toxic relationships. The research employed a quantitative approach using a bivariate correlational design. A total of 139 students who met the criteria for having experienced a toxic relationship participated in the study through purposive sampling. Forgiveness was assessed using the TRIM-18, whereas subjective well-being was measured using the Satisfaction With Life Scale (SWLS) and the Positive and Negative Affect Schedule (PANAS). Pearson’s correlation analysis revealed no significant association between forgiveness and subjective well-being (r = 0.048, p > 0.05). Specifically, forgiveness was not significantly correlated with life satisfaction, positive affect, or negative affect. These findings suggest that forgiveness may not directly contribute to enhanced subjective well-being in the context of toxic relationships. The results underscore the need for more comprehensive and targeted psychological interventions, including therapeutic strategies and emotional support, to aid students in recovering from the adverse effects of toxic relational experiences.